2019
DOI: 10.1002/jcd.21650
|View full text |Cite
|
Sign up to set email alerts
|

Group divisible designs with block size four and type —II

Abstract: We show that the necessary conditions for the existence of group divisible designs with block size four (4‐GDDs) of type g u m 1 are sufficient for g ≡ 0 (mod  h), h = 39, 51, 57, 69, 87, 93, 111, 123 and 129, and for g = 13, 17, 19, 23, 25, 29, 31 and 35. More generally, we show that for g ≡ 3 (mod 6), the possible exceptions occur only when u = 8, and there are no exceptions at all if g ∕ 3 has a divisor d > 1 such that d ≡ 1 (mod 4) or d is a prime not greater than 43. Hence, there are no exceptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
44
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(45 citation statements)
references
References 17 publications
0
44
0
1
Order By: Relevance
“…Assuming mgoodbreakinfix>0 and mgoodbreakinfix≠g, the necessary conditions for the existence of a 4‐GDD of type gum1 are {u4,1emmg(u1)2,gug(u1)+m00.33em(normalmod0.33em3),1emandg2u(u1)+2gum00.33em(normalmod0.33em12), which simplify to ugoodbreakinfix≥4goodbreakinfix,1emmgoodbreakinfix≤g(u1)2goodbreakinfix,1emugoodbreakinfix≡mgoodbreakinfix−ggoodbreakinfix≡00.33em(normalmod0.33em3) when ggoodbreakinfix≡2 or 40.33em(normalmod0.33em6). As for sufficiency, it is convenient to quote [, Theorem 1.2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Assuming mgoodbreakinfix>0 and mgoodbreakinfix≠g, the necessary conditions for the existence of a 4‐GDD of type gum1 are {u4,1emmg(u1)2,gug(u1)+m00.33em(normalmod0.33em3),1emandg2u(u1)+2gum00.33em(normalmod0.33em12), which simplify to ugoodbreakinfix≥4goodbreakinfix,1emmgoodbreakinfix≤g(u1)2goodbreakinfix,1emugoodbreakinfix≡mgoodbreakinfix−ggoodbreakinfix≡00.33em(normalmod0.33em3) when ggoodbreakinfix≡2 or 40.33em(normalmod0.33em6). As for sufficiency, it is convenient to quote [, Theorem 1.2].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the necessary conditions for the existence of 4‐GDDs of type gu, namely, ugoodbreakinfix≥4goodbreakinfix,1emg(u1)goodbreakinfix≡00.33em(normalmod0.33em3)1emand1emg2u(u1)goodbreakinfix≡00.33em(normalmod0.33em12), are known to be sufficient except that there are no 4‐GDDs of types 24 and 64 [ [, Theorem IV.4.6]. The next case one would naturally consider is that of 4‐GDDs of type gum1, and here a partial solution has been achieved in the sense that for each g there are at most a small number of u where existence remains undecided .…”
Section: Introductionmentioning
confidence: 99%
“…The number of exceptions was then reduced to four by Wang and Shen [15]. Wei et al [16] solved two of these four cases, namely m n ( , ) = (6, 7) and (6,11). The last two cases, m n ( , ) = (3, 5) and (4,7), were found by Wang et al [14].…”
mentioning
confidence: 99%
“…Later, Ge and Wei [8] showed that for each pair g t ( , ) there is only a small range of values n for which a 4-GDD of type g n t 1 is unknown whenever the necessary conditions in Lemma 1.1 are satisfied. More recently, Forbes and Forbes [5,6] showed that the necessary conditions are sufficient for a wide class of feasible group types. However, a number of undetermined cases still remain.…”
mentioning
confidence: 99%
See 1 more Smart Citation